A review of the evolution and state of transboundary freshwater treaties - Giordano, Mark; Drieschova, Alena; Duncan, J.A.; Sayama, Y.; Stefano, L. de; Wolf, A.T. (Springer, 2014)
Internationally shared basins supply 60 % of global freshwater supply, are home to about 1/3 of the world’s population, and are focal points for interstate conflict and, as importantly, cooperation. To manage these waters, states have developed a large set of formal treaties, but until now these treaties have been difficult to access and systematically assess. This paper presents and makes publicly available the assembly and organization of the largest known collection of transboundary water agreements in existence. We apply for the first time a “lineage” concept to differentiate between independent agreements and groups of legally related texts, spatially reference the texts to a global basin database, and identify agreement purposes, goals and a variety of content areas. The 688 agreements identified were signed between 1820 and 2007 and constitute 250 independent treaties which apply to 113 basins. While the scope and content varies widely, these treaties nominally govern almost 70 % of the world’s transboundary basin area. In terms of content, treaties have shifted from an earlier focus on regulation and development of water resources to the management of resources and the setting of frameworks for that management. While “traditional” issues such as hydropower, water allocation and irrigation are still important, the environment is now the most commonly mentioned issue in treaty texts. Treaties are also increasingly likely to include data and information sharing provisions, have conflict resolution mechanisms, and include mechanisms for participation beyond traditional nation-state actors. Generalizing, treaties have become more comprehensive over time, both in the issues they address and the tools they use to manage those issues cooperatively.